Portuguese study of mean glandular dose in mammography and comparison with European references - Reis, Cláudia (2018)
To characterize the mean glandular dose (MGD) in a sample of healthcare providers for digital mammography in Portugal. To compare the achieved values with European references. The MGD was measured on a poly-methyl-methacrylate phantom (45 mm) for each system using dosimeters. In addition, MGD was estimated using exposure settings collected from mammography exams in a clinical context. Data were collected from 25 computed-radiography systems (CR) and 13 integrated digital (DR). For both measurements (phantom and clinical exposures), the average MGD for CR was higher compared to the DR. For CR the mean MGD was 1.85 mGy (CC projection) and 2.10 mGy (MLO projection). For DR systems the corresponding values were 1.54 mGy (CC) and 1.68 mGy (MLO). The average MGD obtained using both methods and for both technologies is within the acceptable reference range proposed by European guidelines (<2.5 mGy). Dose Reference Levels implementation should be the next step to optimise mammography practice in Portugal.